PERBEDAAN EFEKTIVITAS EDUKASI GIZI DENGAN MEDIA VIDEO DAN LEAFLET TERHADAP TINGKAT PENGETAHUAN TENTANG ANEMIA PADA REMAJA PUTRI DI MAN 4 JAKARTA TAHUN 2022 - Hana Nabila Noorfajria (2022)
Anemia is a nutritional problem that adolescent girls in Indonesia face. The rising incidence of anemia each year highlights the need for anemia prevention efforts in the form of nutrition education to increase knowledge through the use of media as a tool to facilitate the delivery of material that is easier to understand. This study aims to determine the differences of the effectiveness of nutrition education with videos and leaflets on the level of knowledge about anemia in adolescent girls at MAN 4 Jakarta. This research is a quasi-experimental research with a two pre-post test group design. The total subjects in this study were 76 students in class X and XI which were divided into 2 groups, the video group and the leaflet group, which were selected using stratified random sampling technique. The results of the study using Wilcoxon results showed that there were differences in the level of knowledge about anemia in adolescent girls at MAN 4 Jakarta before and after the intervention with video (p = 0.000) and leaflets (p = 0.000). The results of the study using the Mann-Whitney test showed that there was no difference in the effectiveness of knowledge on nutrition education with videos and leaflets about anemia in adolescent girls (p>0.05).